Bisphenol A exposure triggers apoptosis via three signaling pathways in Caenorhabditis elegans. Issue 52 (27th June 2017) - Wang, Yun; Zhang, Lianfeng; Luo, Xun; Wang, Shunchang; Wang, Yuanyuan
Abstract : Bisphenol A can trigger germline apoptosis via three signaling pathways including DNA damage response (DDR) pathway, mitogen-activated protein kinase (MAPK) cascades and insulin-like growth factor-1 (IGF-1) network in Caenorhabditis elegans . Abstract : Bisphenol A (BPA) is a well-known xenoestrogen that is responsible for multiple adverse effects including reproductive toxicity and apoptosis. However, the mechanism of apoptosis remains elusive. Our present study investigated the mode of BPA's action by evaluating its effect on germline apoptosis in C. elegans . The DNA damage response (DDR) pathway, mitogen-activated protein kinase (MAPK) signaling cascades and insulin-like growth factor-1 (IGF-1) networks were selected as candidates in our model, which may be responsible for BPA-induced apoptosis. The wild type and related mutants were treated with BPA in young adult C. elegans . The results indicate that: (1) in the DDR pathway, both caspase protein CED-3 and Apaf-1 protein CED-4 were required for BPA-induced apoptosis. The apoptosis was blocked by ced-9, and was activated by egl-1 . Checkpoint protein HUS-1 exerted proapoptotic effects, and cep-1, the homologue of p53, also participated in BPA-induced apoptosis. (2) As for MAPK signaling cascades, MAPKKK Raf LIN-45, MAPKK MEK-2/MEK-1/JKK-1 and MAPK JNK-1 may play important roles in the BPA-induced apoptotic process. (3) The results also indicated that IGF-1 network and its target protein DAF-16/FOXO, played important roles in BPA-induced apoptosis. DAF-2/IGF-1R and AKT-1/PKB negatively regulated the apoptosis via DAF-16 induction. Our present studies uncover a signaling network of BPA-induced apoptotic process.